2017
DOI: 10.1126/sciadv.aao2047
|View full text |Cite
|
Sign up to set email alerts
|

Shaping highly regular glass architectures: A lesson from nature

Abstract: Protein crystal branching guides the morphogenesis of glass spicules in marine sponges from the class Demospongiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…The fusion of properties of all of these levels ensures outstanding energy dissipation and resistance to mechanical strain [12][13][14][15][16]. Surprisingly, fabrication of such hierarchical complex glass structures still seems to be far beyond the reach of current human technology [17]. Numerous studies of glass sponges skeletons suggest that the unique fracture toughness results from the spicules cylindrical layered architecture.…”
Section: Siliceous Skeletal Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The fusion of properties of all of these levels ensures outstanding energy dissipation and resistance to mechanical strain [12][13][14][15][16]. Surprisingly, fabrication of such hierarchical complex glass structures still seems to be far beyond the reach of current human technology [17]. Numerous studies of glass sponges skeletons suggest that the unique fracture toughness results from the spicules cylindrical layered architecture.…”
Section: Siliceous Skeletal Frameworkmentioning
confidence: 99%
“…Over the last decades numerous research groups analyzed the organic constituents involved in spiculogenesis and supporting formation of sophisticated glass sponge constructs. According to the present state of art, four different organic templates that may be involved in biosilicification in glass sponges were isolated and proposed: silicateins [17,23], glassin [24], collagen [25] and chitin [26,27]. The silicatein-and glassin-based hypotheses are in conflict with the proposed role of collagen and chitin as alternative templates in spicule formation in glass sponges (for details please see [7]) and became a serious bone of contention between various research groups.…”
Section: Siliceous Skeletal Frameworkmentioning
confidence: 99%
“…Astonishingly, being composed of an inherently disordered amorphous material, these skeletal elements exhibit a variety of highly regular species-specific branched morphologies and are considered a paradigm of symmetry in biomineralized systems ( 9 ). A recent study revealed that this order is realized with the assistance of axial filaments that pass through the center of every branch in every spicule and direct silica deposition ( 10 ). The filaments in demosponges were demonstrated to be perfect slender protein crystals, and their branching on well-defined crystallographic planes of that crystal was shown to be responsible for the high spatial regularity and symmetry of the spicules.…”
mentioning
confidence: 99%
“…In contrast, the crystalline assembly of silicatein units in vivo, inside the axial filaments of demosponges, such as T. aurantium , is well recorded by a number of recent X-ray diffraction and transmission electron microscopy studies ( 10 , 24 26 ). The marine sponge T. aurantium ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation